The views and experiences of school leaders implementing whole school relational approaches in a single secondary school: A Reflexive Thematic Analysis - Dodds, Jessica Fay (2023)
Reflexive Thematic Analysis (RTA, Braun & Clarke, 2021a) was utilised to explore the views and experiences of school leaders (SLs) implementing whole school relational approaches.